Peppermint essential oil enhances the vase life of Dendrobium orchids - Montinee Teerarak; Komkhae Pilasombut; Chamroon Laosinwattana (My University, 2024)
To extend the vase life of cut flowers, there is now a trend of using plant essential oils in place of synthetic chemicals, as they are fully biodegradable, more eco-friendly, and safer. The objective of this study was to examine the possible application and postharvest quality effects of three plant essential oils namely, ginger (Zingiber officinale Roscoe), peppermint (Mentha piperita L.), and citronella (Cymbopogon nardus Rendle), as natural vase solution for cut Dendrobium flowers. Peppermint essential oil showed promise as a holding solution for extending the vase life of Dendrobium orchids. To confirm vase life extension, emulsions containing peppermint essential oil at concentrations of 50 and 100 μg mL-1 combined with 4% glucose to formulate holding solutions applied to Dendrobium orchids. Vase life, some biochemical changes, electrolyte leakage, total microbial count in the holding solution, and physical condition via scanning electron microscopy (SEM) were evaluated over a period of 25 days. The three major compounds in peppermint essential oil were identified as menthol (33.24%), 1-menthone (18.91%) and menthofuran (14.85%). The essential oil was applied in emulsion form as a holding solution. Treatment with 4% glucose and either 50 or 100 μg mL-1 peppermint essential oil prolonged the vase life of Dendrobium orchids to up to 28 days. Scanning electron microscopy on Day 7 showed that the xylem vessels of treated orchids remained clear, suggesting reduced microbial plugging at the stalk end. Similarly, on Day 20, a reduced microbial cell count was observed for treated orchids (<1 log CFU mL-1) in comparison with controls (7.20±0.04 log CFU mL-1). Finally, the essential oil improved flower quality by helping preserve petal membrane stability and petal anthocyanin content. Our results suggest the application of peppermint essential oil as a novel alternative to chemicals used in holding solutions for extending the vase life of Dendrobium orchids.
Keywords: Dendrobium; Vase life; Vase; Cut flowers; Essential Oils and Antimicrobial Activity